Evaluation of storage time and temperature on physicochemical properties of immersion vacuum cooled sausages stuffed in the innovative casings modified by surfactants and lactic acid - Feng, Chao-Hui; Wang, Wei; Makino, Yoshio; García-Martín, Juan Francisco; Alvarez-Mateos, Paloma; Song, Xiao-Yan (Journal of food engineering, 2019)
The combined effects of different storage temperatures (0, 4, 10 °C) and days (3, 8, 16, 25, 35, 46 and 58 days), and the use of modified casings on sausages cooled by immersion vacuum cooling (IVC) were investigated. Sausages were firstly cooked at 72 °C and cooled to 4 °C by IVC. Texture profile, colour, pH, moisture and volatile composition of samples were measured during 58-d storage. Hardness of samples with modified casings stored at 4 °C (MIVC-4 oC) at d8 (75.28 ± 6.05 N) was significantly higher than that at d3 (38.09 ± 8.89 N) (P < 0.05). According to the electronic nose analysis, modified casing sausages stored at 0 °C (MIVC-0 oC) can be distinguished from those treated by MIVC-4 oC and MIVC-10 °C during all the 58-day storage but at d16. The temperature fluctuation (0–10 °C) during the cold-chain transportation or retail distribution can affect both quality and volatile composition. •Combined effects of different storage temperatures, days and modified casings were studied.•Simple effect analysis was used for the first time to interpret the interaction relationship.•Modified casings greatly affected gumminess and colour (L∗, a∗, b∗).•Moisture and pH were considerably influenced by different storage temperatures.•Modified casing sausages stored at 0 °C can be distinguished according to volatile composition.